MENINGKATKAN HASIL BELAJAR CHEST PASS BOLA BASKET MELALUI PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS-ACHIEVEMENT DIVISIONS PADA SISWA KELAS VI SD MUHAMMADIYAH 3 KECAMATAN BANJARSARI KOTA SURAKARTA TAHUN PELAJARAN 2012/2013 - Indarto, Joni (Jurnal Phederal Penjas, 2013)
This study uses classroom action research or Classroom Action Research that consists of four stages: planning, implementation, observation and reflection in each cycle and the study was completed in two cycles. Subjects in this study were students of class VI 3 SD Muhammadiyah Surakarta City District Banjarsari school year 2012/2013, amounting to 43 students consisting of 25 boys and 18 girls students. The data were obtained through observations by researchers and collaborators during the learning process takes place. The data is the result of learning basketball chest pass students gained through observation sheets covering the cognitive, the affective and psychomotor domains. Data analysis in this study used a descriptive analysis using percentage technique to look at trends in learning activities. Based on these results it can be concluded that the learning model student teams-achievement divisions can improve learning outcomes basketball chest pass in class VI 3 SD Muhammadiyah Surakarta City District Banjarsari school year 2012/2013, in which the learning outcomes in the initial conditions or 39.53% 17 students, at the end of the first cycle to be 60.46%, or 26 students, and at the end of the second cycle to be 83.72% or 36 students. Keywords: learning outcomes, basketball chest pass, a model student learning teams-achievement divisions